Mathematical Literacy Viewed from Self-Efficacy through Creative Problem Solving Learning Assisted by Google Classroom - Rahmah, Rahmah; Wardono, Wardono; Sugiman, Sugiman (research, training and philanthropy institution Natural Aceh, 2024)
This study aims to determine the influence of implementing Creative Problem Solving assisted by Google Classroom on students' mathematical literacy based on Self-efficacy. The research method employed is quasi-experimental. The study population consists of all seventh-grade students at MTsN 3 West Aceh. The research sample includes Class VII B as the experimental group and Class VII F as the control group. Quantitative data were analyzed using statistical tests processed with IBM SPSS Statistics 16. The research findings indicate (1) the average mathematical literacy of students in the experimental group, who received Creative Problem Solving assisted by Google Classroom, was higher than that of students in the control group who received Discovery Learning, with a calculated t-value of 5.75 > critical t-value of 1.99 using a one-tailed test for the difference in means; (2) the increase in mathematical literacy among students in the experimental group, who received Creative Problem Solving assisted by Google Classroom, was greater than that of students in the control group who received Discovery Learning, with a calculated t-value of 2.89 > critical t-value of 1.99 using an improvement test; and (3) Self-efficacy positively influenced the mathematical literacy of students in the experimental group who received Creative Problem Solving assisted by Google Classroom, accounting for 49.4% of the influence using an influence test. Based on the research, Creative Problem Solving assisted by Google Classroom proves effective in enhancing students' mathematical literacy in schools.